Cobalt metal–organic framework derived cobalt–nitrogen–carbon material for overall water splitting and supercapacitor. (26th March 2023) - Gupta, Anjali; Allison, Cassia A.; Ellis, Madeline E.; Choi, Jonghyun; Davis, Allen; Srivastava, Rishabh; de Souza, Felipe M.; Neupane, Dipesh; Mishra, Sanjay R.; Perez, Felio; Kumar, Anuj; Gupta, Ram K.; et al.
Abstract: Metal-organic frameworks (MOFs) have been the subject of intensive structural tuning via methods like pyrolysis for superior performance in electrocatalytic oxygen and hydrogen evolution processes (OER and HER) and supercapacitors. Here, a Co-MOF based on 2-methylimidazole was synthesized using a precipitation approach, and its electrochemical characteristics were tuned via pyrolysis at different temperatures, including 600, 700, and 800 °C. Characterization findings corroborated the formation of Co–N–C moieties from Co-MOF, and XPS analyses indicated that 700 °C was the optimal temperature for achieving a high density of Co–N–C moieties. The optimized Co-MOF-700 sample displayed remarkable HER and OER performance in terms of lower overpotentials of 75 mV and 370 mV as well as small Tafel slopes of 118 mV/dec and 79 mV/dec, respectively. Furthermore, at a current density of 1 A/g, the Co-MOF-700 sample had a specific capacitance of 210 F/g. The enhanced electrochemical properties of Co-MOF-700C as compared to other samples can be attributed to the availability of a high density of Co–N–C sites for catalytic reaction and its porous architecture. This study will expand the knowledge of how compositional and morphological changes in MOFs affect their utility in energy conversion and storage applications. Graphical abstract: Image 1 Highlights: The electrochemistry of Co-MOF was tuned via pyrolysis at different temperatures. The optimized Co-MOF-700 sample displayed remarkable HER and OER performance. Theoretical calculations were carried out to reveal the mechanisms of HER and OER.